Familial vs. sporadic sarcoidosis: BTNL2 polymorphisms, clinical presentations, and outcomes in a French cohort. Issue 1 (December 2016) - Pacheco, Yves; Calender, Alain; Israël-Biet, Dominique; Roy, Pascal; Lebecque, Serge; Cottin, Vincent; Bouvry, Diane; Nunes, Hilario; Sève, Pascal; Pérard, Laurent; Devouassoux, Gilles; Freymond, Nathalie; et al.
Abstract Background The occurrence of familial forms of sarcoidosis (OMIM 181100) suggests a genetic predisposition. The involvement of butyrophilin-like 2 (BTNL2) gene (rs2076530 variant) has to be investigated. Results The study performed independent analyses of BTNL2 polymorphism, clinical phenotypes, and outcomes in familial vs. sporadic presentations in 256 sporadic and 207 familial cases from 140 families. The logistic multivariate model showed that a young age at diagnosis and the combination of lung and skin involvement at diagnosis may distinguish sporadic from familial sarcoidosis (p = 0.016 andp = 0.041). We observed also that Sarcoid Clinical Activity Classification (SCAC) profiles were significantly different between familial and sporadic cases (p = 0.0497). Variant rs2076530 was more frequent in patients than in controls (OR = 2.02; 95% CI: [1.32–3.09]) but showed no difference between sporadic and familial cases and no difference according to the clinical phenotype or the outcome. Conclusion Despite a significant difference in BTNL2 polymorphism between sarcoid patients and controls, there was no such difference between familial and sporadic sarcoidosis cases and no correlation between BTNL2 polymorphism and disease severity or outcome. Thus, BTNL2 difference cannot be considered as a key marker for disease classification or patient management.